2016
DOI: 10.3389/fpls.2016.01054
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNAs and Their Target Genes Explores miRNA-Mediated Regulatory Network of Cytoplasmic Male Sterility Occurrence during Anther Development in Radish (Raphanus sativus L.)

Abstract: MicroRNAs (miRNAs) are a type of endogenous non-coding small RNAs that play critical roles in plant growth and developmental processes. Cytoplasmic male sterility (CMS) is typically a maternally inherited trait and widely used in plant heterosis utilization. However, the miRNA-mediated regulatory network of CMS occurrence during anther development remains largely unknown in radish. In this study, a comparative small RNAome sequencing was conducted in floral buds of CMS line ‘WA’ and its maintainer line ‘WB’ by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 78 publications
2
25
0
Order By: Relevance
“…Increasing evidence shows that miRNAs are vital components of the posttranscriptional regulation of gene expression, which is important for almost all aspects of plant biological development, such as tissue differentiation, signal transduction, growth phase switching, and response to stresses (Vance and Vaucheret 2001;Baulcombe 2004;Millar and Gubler 2005;Xie and Qi 2008;Li et al 2011;Soitamo et al 2012;Yang et al 2013a, b, c;Cui et al 2014;Kontra et al 2016;Liu and Chen 2016;Adkar-Purushothama et al 2018;Li and Wang 2018;Zhang et al 2018Zhang et al ,2019Sun Sparks et al 2019). Recently, with the rapid development of high-throughput sequencing technology, several studies have identified miRNAs and their target genes on a genomewide level in crops during anther development (Chambers and Shuai 2009;Wei et al 2013a, b;Yang et al 2013aYang et al , b, c, 2016Jiang et al 2014;Zhang et al 2016Zhang et al ,2018. For example, a comparative miRNAome analysis was performed between CMS and maintainer lines in Raphanus sativus, and 28 known and 14 potential novel miRNAs were detected to be differentially expressed, revealing a putative regulatory network involved in anther development (Zhang et al 2016).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Increasing evidence shows that miRNAs are vital components of the posttranscriptional regulation of gene expression, which is important for almost all aspects of plant biological development, such as tissue differentiation, signal transduction, growth phase switching, and response to stresses (Vance and Vaucheret 2001;Baulcombe 2004;Millar and Gubler 2005;Xie and Qi 2008;Li et al 2011;Soitamo et al 2012;Yang et al 2013a, b, c;Cui et al 2014;Kontra et al 2016;Liu and Chen 2016;Adkar-Purushothama et al 2018;Li and Wang 2018;Zhang et al 2018Zhang et al ,2019Sun Sparks et al 2019). Recently, with the rapid development of high-throughput sequencing technology, several studies have identified miRNAs and their target genes on a genomewide level in crops during anther development (Chambers and Shuai 2009;Wei et al 2013a, b;Yang et al 2013aYang et al , b, c, 2016Jiang et al 2014;Zhang et al 2016Zhang et al ,2018. For example, a comparative miRNAome analysis was performed between CMS and maintainer lines in Raphanus sativus, and 28 known and 14 potential novel miRNAs were detected to be differentially expressed, revealing a putative regulatory network involved in anther development (Zhang et al 2016).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…This link between RNA editing and CMS is not ubiquitous for all plants (Horn et al, 2014). Finally, recent degradome sequencing implicates a possible role for microRNAs in the regulatory network of Brassica juncea and Raphanus sativus CMS Zhang et al, 2016).…”
Section: Regulation Of Cms Transcripts Via Rna Editingmentioning
confidence: 99%
“…█ INTRODUCTION C erebral infarction is a type of cerebrovascular disease caused by a cerebral blood supply disorder. Severe disturbance of consciousness, sensory and motor dysfunction, neurodegenerative diseases, and even sudden death often occurat the onset of cerebral infarction (17,18,33). It has been reported that cerebral infarction has become a leading cause of disability and death worldwide because of its high morbidity and mortality (9,12).…”
Section: Original Investigationmentioning
confidence: 99%